Target Site Insensitivity Detection in Deltamethrin Resistant Culex pipiens Complex in Iran - Reza ZEIDABADINEZHAD; Hassan VATANDOOST; Mohammad Reza ABAI; Navid DINPARAST DJADID; Abbasali RAZ; Mohammad Mahdi SEDAGHAT; Mohamad Ali OSHAGHI; Ahmad RAEISI; Neda ADIBI (Tehran University of Medical Sciences, 2019)
Background: Some mosquito species which belong to the Culex. pipiens complex are primary vectors for West Nile virus, Sindbis, Dirofilaria immitis, and many arboviruses. Knockdown resistance (kdr) mutations in the voltage-gated sodium channel (VGSC) gene of Cx. pipiens that is inherited, is one of the important threats for the efficacy of pyrethroids insecticides. Knockdown resistance (kdr) mutation, L1014F, is a well-defined mechanism of resistance to pyrethroids and DDT in many insect species. The aim of study was to determine the mechanisms of Insecticide resistance in this species Methods: Specimens of Cx. pipiens, the major vector of West Nile virus, were obtained in Tehran, Iran by collecting larvae from polluted wastewater in Qarchak of Tehran. In 2016 Insecticide susceptibility tests were performed according to WHO methods with deltamethrin 0.05%. We focused on determination of this point mutation in the VGSC gene of Cx. pipiens by Real-time PCR. Results: Our results revealed high levels of resistance to deltamethrin 0.05%. The lethal times i.e. LT50 and LT90 for deltamethrin were 2.1530 and 8.5117 h respectively. The result of Real-time PCR confirmed the presence of resistant genotype in all the members of tested population. This study is the first report on kdr genotyping of Cx. pipiens from Tehran and our results on the VGSC gene in position L1014F confirmed the TTA to TTT nucleotide change. Conclusion: This finding will provide a clue for management of insecticide resistance in mosquito which are vectors of arboviruses and decision for replacement of novel approach for vector control.